Protocol for a pilot randomised controlled trial of metformin in pre-diabetes after kidney transplantation: the Transplantation and Diabetes (Transdiab) study. Issue 8 (23rd August 2017) - Alnasrallah, Basil; Pilmore, Helen; Manley, Paul
Abstract : Introduction: Post-transplant diabetes mellitus (PTDM) is a common complication of kidney transplantation and is associated with significant morbidity and mortality. In the general population, metformin has been used for diabetes prevention in high-risk individuals. Improving insulin sensitivity is one of many proven favourable effects of metformin. Despite the high incidence of PTDM in kidney transplant recipients, there is a lack of evidence for the role of metformin in the prevention of diabetes in this setting. Methods and analysis: Trans plantation and Diab etes (Transdiab) is a single-centre, unblinded, pilot randomised controlled trial assessing the feasibility, tolerability and efficacy of metformin after renal transplantation in patients with impaired glucose tolerance (IGT). Participants will undergo an oral glucose tolerance test in the 4–12 weeks post-transplantation; those with IGT will be randomised to standard care or standard care and metformin 500 mg twice daily, and followed up for 12 months. The primary outcomes of the study will be the feasibility of recruitment, the tolerability of metformin assessed using the Gastrointestinal Symptom Rating Scale at 3 and 12 months, and the efficacy of metformin assessed by morning glucose and glycated haemoglobin at 3, 6, 9 and 12 months. Ethics and dissemination: Despite the significant morbidity and mortality of PTDM, there are currently no randomised clinical trials assessing pharmacological interventions for its prevention after kidney transplantation. The Transdiab trial will thus provide important data on the feasibility, safety, tolerability and efficacy of metformin after renal transplantation in patients with IGT; this will facilitate undertaking larger multicentre trials of interventions to reduce the incidence or severity of diabetes after kidney transplantation. This study has been approved by the Northern B Health and Disability Ethics Committee of the Ministry of Health in New Zealand. On study completion, results are expected to be published in a peer-reviewed journal. Trial registration number: Australian New Zealand Clinical Trials Registry Number: ACTRN12614001171606.